fMRI-based explanations for how meditation could modulate pain processing - Golshan, Faly; Mickleborough, Marla J. S. (Frontiers in Neuroscience, 2025)
Meditation is a widely recognized umbrella term encompassing a diverse range of techniques with shared foundational characteristics, celebrated for their potential to alleviate mental and physical challenges. While subjective reports and behavioral studies have long highlighted meditation’s benefits, recent neuroscientific research has sought to provide tangible physiological evidence of its efficacy as a non-invasive intervention for managing physical pain. This review examines the neurophysiological mechanisms by which meditation influences brain activity in response to both acute and chronic pain experiences. Drawing on findings from functional magnetic resonance imaging (fMRI) studies, general models are categorized to explain how meditation alters cortical responses in both naïve and expert practitioners when exposed to pain stimuli. First, we discuss three major components of pain processing in the brain and analyze how meditation affects each stage. Next, we identify key brain regions consistently implicated in pain modulation through meditation, elucidating their roles in pain perception and regulation. Finally, we propose a framework for differentiating meditation techniques based on their distinct effects on pain experiences. These insights have significant implications for understanding the therapeutic potential of various meditation techniques for pain management, particularly in chronic conditions.